Bacterial communities associated with invasive populations of Bactrocera dorsalis (Diptera: Tephritidae) in China. Issue 6 (31st May 2016) - Liu, L.J.; Martinez-Sañudo, I.; Mazzon, L.; Prabhakar, C.S.; Girolami, V.; Deng, Y.L.; Dai, Y.; Li, Z.H.
Abstract: The oriental fruit fly Bactrocera dorsalis (Hendel) is a destructive insect pest of a wide range of fruits and vegetables. This pest is an invasive species and is currently distributed in some provinces of China. To recover the symbiotic bacteria of B. dorsalis from different invasion regions in China, we researched the bacterial diversity of this fruit fly among one laboratory colony (Guangdong, China) and 15 wild populations (14 sites in China and one site in Thailand) using DNA-based approaches. The construction of 16S rRNA gene libraries allowed the identification of 24 operational taxonomic units of associated bacteria at the 3% distance level, and these were affiliated with 3 phyla, 5 families, and 13 genera. The higher bacterial diversity was recovered in wild populations compared with the laboratory colony and in samples from early term invasion regions compared with samples from late term invasion regions. Moreover, Klebsiella pneumoniae and Providencia sp. were two of the most frequently recovered bacteria, present in flies collected from three different regions in China where B. dorsalis is invasive. This study for the first time provides a systemic investigation of the symbiotic bacteria of B. dorsalis from different invasion regions in China.